Bilateral Cavernous Sinus Thrombosis in a Patient with Tacrolimus-Associated Posttransplant Thrombotic Microangiopathy. Issue 1 (January 2017) - Kolomeyer, Anton M.; Nischal, Ken K.; Mitchell, Ellen
Purpose: To report a case of bilateral cavernous sinus thrombosis (CST) in a patient with tacrolimus-associated posttransplant thrombotic microangiopathy. Methods: Case report. Results: An 8-year-old boy with a medical history of orthotopic heart transplant, posttransplant lymphoproliferative disease, and recurrent infections was hospitalized for nausea, vomiting, and diarrhea. His ocular history included accommodative esotropia, hyperopia with astigmatism, Molluscum contagiosum lid lesions, and idiopathic intracranial hypertension. Shortly after presentation, he developed increased intraocular pressure, an afferent pupillary defect, a layered hyphema, and tense proptosis of the left globe requiring an emergent canthotomy and cantholysis. Over the next month, the patient's hospital course included subdural and subarachnoid hemorrhage, temporal lobe stroke, serotonin syndrome, bilateral CST, and systemic microangiopathy. After an extensive workup, a diagnosis of tacrolimus-associated thrombotic microangiopathy was made. At this point, vision was 20/20 in the right eye and light perception in the left eye. Eight months after the canthotomy and cantholysis, the patient's vision in the left eye deteriorated to no light perception and remained so after 13 months of follow-up. Conclusions: An idiosyncratic drug reaction should be considered in the differential diagnosis of CST, especially in a patient on calcineurin inhibitors after solid organ transplant without sinus disease or orbital cellulitis.